Granulocyte colony-stimulating factor gene rs1042658 variant and susceptibility to idiopathic recurrent pregnancy loss: A case-control study - Mahboobeh Nasiri; Kobra Jahangirizadeh (Shahid Sadoughi University of Medical Sciences, 2018)
Background: Granulocyte colony-in stimulating factor (G-CSF) gene can be a potential candidate gene implicated recurrent pregnancy loss (RPL), a common complication of pregnancy with the prevalence of 1-5% among women of reproductive age. Objective: To investigate the association between rs1042658 polymorphism in the 3' untranslated region (3'UTR) of G-CSF gene and the risk of unexplained RPL among Iranian women. Materials and Methods: In total, 122 women with unexplained RPL and 140 healthy postmenopausal women as a control group were enrolled in this case-control study. Tetra-primer amplification refractory mutation system-polymerase chain reaction was performed to determine the rs1042658 genotypes in all subjects. Results: Statistically significant differences were detected between the distribution frequencies of both heterozygote CT, and carriage of T allele (TT+CT) genotypes of the rs1042658 between case and control groups. Allelic association was not observed with RPL. Conclusion: Regarding the results of the present study, G-CSF rs1042658 gene polymorphism could be considered as a probable risk factor for unexplained RPL among Iranian women.